The Relationship between Consumers' Level of Acculturation to the Global Consumer Culture and Perception of Different Types of Consumer Culture Positioning - An Investigation of the Beer Brands in Taiwan - Chang, Jo-Heng (2007)
This research is essentially concerned with the relationship between consumer acculturation to the global consumer culture (AGCC) and consumer culture positioning. These two constructs are both derived from the literatures of the global consumer culture. Previous researches on AGCC are based on the consumer acculturation studies on the immigrant consumers' adaptation to the host country, combined with theories of cultural values, consumer ethnocentrism, and country of origin effect. Consumer culture positioning is identified by Alden et al. (1999). They proposed the global consumer culture positioning (GCCP) in contrast to two other positioning, namely, the foreign consumer culture positioning (FCCP) and the local consumer culture positioning (LCCP). Moreover, because previous studies on the realm of the global consumer culture are mainly by Western scholars, this study focuses on the Taiwanese consumers to explore more understanding of consumers in a non- western context. For developing an in-depth understanding of consumers' insights on this issue, qualitative approach was employed in the form of depth- interviews. The interviews are conducted in two stages, centring on consumers' perception of AGCC and different types of consumer culture positioning respectively. Through the thorough analysis of the interview data, the findings reveal that consumers' level of AGCC is relevant with consumers' diagnosis of different types of consumer culture positioning. Moreover, some factors of AGCC identified by previous of literature are found more meaningful than the others to Taiwanese consumers. Besides, some dimension used to classify the different types of consumers culture positioning are pointed out to be less pertinent in this research context. Lastly, it is disclosed by this research that consumers acknowledge the uniformity led by globalization, but it is the variety of choices that is considered beneficial to the consumers.